ANALISIS INTERVENSI KENAIKAN HARGA BBM TERHADAP PERMINTAAN BBM BERSUBSIDI PADA SPBU SULTAN AGUNG SEMARANG JAWA TENGAH - Fandi Ahmad; Rita Rahmawati; Diah Safitri (Jurnal Gaussian, 2015)
Fuel consumption is always interesting to study, in addition to the use of which is used by all the community but also because of the critical role of fuel as an indicator to determine the price of other staples. Not surprisingly, changes in fuel prices polemical definitely interesting to study. In this subject specifically on the impact of the fuel price hike subsidized fuel demand. Changes in fuel price (hike) will have an impact on people's behavior in anticipation of the event. Most people will take the step to buy fuel in bulk prior to the date of determination of the increase in fuel prices, resulting in a surge in demand for fuel. Intervention model is a time series model that can be used to model and predict the data containing the intervention of external factors. In the intervention model, there are two functions, namely the step and pulse functions. Step function is a form of intervention that occurs within a long period of time while the pulse function is a form of intervention that occurs only within a certain time. Based on the analysis suggests that the impact of the use of gasoline and diesel at the pump Sultan Agung Semarang wear both pulse function because the impact was immediate and occur only in a short time                                                                                                                                      Keywords: subsidized BBM, time series, intervention models, pulse function, step function